Some New Contra-Continuous Functions in Topology - Page, Md. Hanif; Patil, P. G. (Communications in Mathematics and Applications, 2016)
In this paper we apply the notion of sgp-open sets in topological space to present and study a new class of functions called contra and almost contra sgp-continuous functions as a generalization of contra continuity which was introduced and investigated by Dontchev [5]. We also discuss the relationships between them and with some other related functions.